Implementasi Asas Amar Ma’ruf Nahi Munkar dalam Qanun Jinayah Aceh: Antara Penegakan Syariat dan Keadilan Sosial - Aji Santoso; Aulia Rahman Fahrudin; Adieb Aunurafiq; Agung Nugraha Putra; Deden Najmudin (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
Qanun Jinayah Aceh is a form of application of Islamic law in the regional legal system which is based on the principle of amar ma'ruf nahi munkar. This principle aims to uphold moral values ​​and prevent deviant acts in society. However, its implementation cannot be separated from containing the limits of sharia enforcement, protection of human rights, and the realization of social justice. This condition shows the need for a critical study of the application of the principles of amar ma'ruf nahi munkar in the Aceh Qanun Jinayah. This study aims to analyze the implementation of the principle of amar ma'ruf nahi munkar in the Aceh Qanun Jinayah and assess its conformity with the principles of social justice. The research method used is normative juridical with a statutory, conceptual, and sociological approach, through a literature study of regulations, Islamic legal literature, and related scientific studies. The results of the study indicate that the principle of amar ma'ruf nahi munkar has become the normative basis for enforcing the Qanun Jinayah, but in practice it still faces challenges in the form of law enforcement that is not fully fair, potential discrimination, and a weak perspective on social justice. Therefore, the implementation of these principles must be proportional, contextual, and oriented toward the public interest. The implications of this research emphasize the importance of integrating the enforcement of Islamic law with the principles of social justice so that the Aceh Qanun Jinayah can be implemented fairly, humanely, and sustainably.